Innovation Technology and Pedagogy in English Language Classroom: Opportunities and Challenges in Vocational Education - Beni Wijaya; Darmaliana Darmaliana; Zakaria; Sri Endah Kusmartini; Eli Yeny; Amalia Hayyu Alditria; Nafizsha Donna Rienvillia; Syavira Riski Eriyanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
As vocational English emphasizes authentic workplace communication and digital literacy, this study examined integration of innovation technology and pedagogy in a vocational school. It investigated how vocational English teachers used technology innovation in the classroom, the opportunities it offered to help students become more proficient in the language, and the challenges encountered when putting it into practice. Fifteen English teachers of SMKN 2 Palembang, Indonesia, became the participants. A descriptive qualitative method was used as interviews, observations in the classroom, and documentation were conducted to gather data. The results of thematic analysis demonstrated how they incorporated interactive learning platforms, internet applications, and multimedia presentations into their lesson plans. Furthermore, it facilitated real-world, student-centered learning opportunities related to professional communication requirements and vocational contexts. There were still a number of issues, such as inadequate technology resources, inadequate training for teachers, erratic internet access, and disparities in students' digital competence. This study contributes to vocational English education by showing how innovative technology and pedagogy improve students' communication skills, learning engagement, and workplace preparedness while addressing the implementation challenges.